Features of the mixing of water and ethanol under alternating pressure pulses - Дубовкіна, Ірина Олександрівна (Technology audit and production reserves, 2015)
Analytical studies of ways of mixing water and ethanol are conducted. Energy-saving method is proposed for the continuous mixing of water and ethanol under alternating pressure pulses. Rational thermophysical modes of the continuous process of mixing water and ethanol under alternating pressure pulses are chosen. The study of physical and chemical properties of the resulting mixtures is conducted. These results demonstrate the feasibility of using the power saving mode continuous mixing of water and ethanol in the conditions of alternating pressure pulses for food pharmaceutical and cosmetic industries. Based on experimental studies, numerical experiments and field tests proposed rational technological modes of carrying out continuous mixing of water and ethanol in the conditions of alternating pressure pulses. When using the technology of production for water-ethanol mixtures in conditions of alternating pressure pulse is intense impact stress shear, shear flow, a high-frequency oscillation, which leads to reduction of quantity of harmful impurities.